Safety and immunogenicity of full-dose quadrivalent influenza vaccine in children 6-35 months of age in China: A randomized, double-blind, clinical trial - Shilei Wang; Yanxia Wang; Dandan Chen; Wenting Xu; Peng Duan; Wei Ji; Weijun Liu; Weijin Huang; Bing Wu; Wenqing Chai; Chenyan Zhao; Yongli Yang; et al. (Taylor & Francis Group, 2024)
A half-dose influenza vaccine (7.5 μg hemagglutinin per strain) has been used for children under 3 years of age for a long time. However, several studies indicate that a full-dose influenza vaccine (15 μg hemagglutinin per strain) may bring more benefit to this population without increasing the risk of adverse reactions. We conducted a clinical study in children aged 6-35 months in China. Participants were randomized to receive two doses of full-dose quadrivalent influenza vaccine (F-QIV), half-dose quadrivalent vaccine (H-QIV), and two half-dose trivalent vaccines (H-TIV) in a 2:2:1:1 ratio. The safety and tolerability profile of the vaccine was evaluated for 6 months postvaccination. Hemagglutination inhibition (HI) antibody titers were measured for immunogenicity assessment. The primary objective was to assess whether the results of all vaccines met the criteria. A total of 1,980 participants were enrolled in the study. Both H-QIV and F-QIV were well tolerated after vaccination. Although the geometric mean increase (GMI), seroconversion rate (SCR), and seroprotection rate (SPR) for both H-QIV and F-QIV were achieved by the criteria, superior immunogenicity in terms of geometric mean titer (GMT) ratio was observed in F-QIV to H-QIV for A/H3N2 (GMT ratio (95% CI) of 1.37 (1.11 ~ 1.68)) and B/Yamagata (1.21 (1.05 ~ 1.39)). Antibody responses to the QIV were non-inferior to the response to the TIV for the matched strains. In conclusion, F-QIV and H-QIV were both safe and immunogenic for children. F-QIV induced a stronger immune response to influenza viruses and may provide more protection and benefit by promoting the use of F-QIV in children aged 6-35 months.